Dialogical and Transversal Translation: Trespassing Cultural Boundaries and Making the Self through Language - Fathi, Mastoureh (Narrative Works, 2013)
This paper draws on two points about the difficulties of conducting research between two languages and cultures which are scant in social science research: one is reflecting on the notion of “making sense” and how prevalent it has become to make sense for a western audience. This process is complicated and leads to more meanings lost in translation, so it is important to unpack it specifically during the research process. The second point I discuss in this paper is the notion of “situated auto/biography” that is not specific to an author or a researcher, but deals with all parties involved in the process of knowledge production. I argue that translation acts as a creative space for thinking and not just conveying meanings, but that through a dialogical and transversal act, it can help in creating new meanings.